2015
DOI: 10.1016/j.freeradbiomed.2015.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Nrf2 in cell proliferation and differentiation

Abstract: The Keap1-Nrf2 system plays pivotal roles in defense mechanisms by regulating cellular redox homeostasis. Nrf2 is an inducible transcription factor that activates a battery of genes encoding antioxidant proteins and phase II enzymes in response to oxidative stress and electrophilic xenobiotics. The activity of Nrf2 is regulated by Keap1, which promotes the ubiquitination and subsequent degradation of Nrf2 under normal conditions and releases the inhibited Nrf2 activity upon exposure to the stresses. Though an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
140
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(148 citation statements)
references
References 156 publications
4
140
0
Order By: Relevance
“…Perhaps Keap1 arose in higher organisms to broaden or speed responsiveness to diverse electrophilic compounds. Nrf2 is either pathogenic or protective in certain cancers, diabetes, and other diseases (Murakami and Motohashi, 2015; O’Connell and Hayes, 2015; Uruno et al, 2013). It will be important to elucidate the extent to which the normal and disease-related functions of Nrf2 involve its regulation by Ire1α, and ER-associated ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps Keap1 arose in higher organisms to broaden or speed responsiveness to diverse electrophilic compounds. Nrf2 is either pathogenic or protective in certain cancers, diabetes, and other diseases (Murakami and Motohashi, 2015; O’Connell and Hayes, 2015; Uruno et al, 2013). It will be important to elucidate the extent to which the normal and disease-related functions of Nrf2 involve its regulation by Ire1α, and ER-associated ROS.…”
Section: Discussionmentioning
confidence: 99%
“…The KEAP1-NRF2 system has been shown to regulate cell proliferation and differentiation through the modulation of ROS levels in certain types of cells (9). Although ROS are required for HSPC proliferation and are increased upon the initiation of HSPC proliferation (33,34), excessive accumulation of ROS causes the functional decline of HSCs (35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to redox regulation, recent studies have revealed critical contributions of the regulatory networks governed by NRF2 to a wider range of biological processes (9). In particular, the NRF2-mediated regulation of cell proliferation and differentiation has gained attention as a possible mechanism by which environmental stress can influence cell fate determination.…”
mentioning
confidence: 99%
“…Activation of the NRF2 signaling pathway and its downstream factors, such as GSTP and NQO1, plays a vital role in the antioxidant activities3637. A recent study suggests that the activation of the endogenous NRF2 signaling pathway and the subsequent increases of antioxidant responsive element (ARE) members is an efficient and new approach for the exploration of next generation of antioxidants, which are different from the traditional and classic small molecule antioxidants which have potential side effects in clinical application34.…”
Section: Discussionmentioning
confidence: 99%